FLIPPED CLASSROOM IN ARTS: STRATEGIES AND IMPACTS ON THE TEACHING-LEARNING PROCESS: Flipped classroom in arts: strategies and impacts on the teaching-learning process - Leal, Deuzilene Machado Rocha (2024)
This article aims to analyze the application of the flipped classroom methodology in arts education, investigating its strategies and impacts on the teaching-learning process. The research adopts a qualitative approach, through a bibliographic review, highlighting authors who deal with active methodologies, such as Rodrigues (2023), Bacich and Moran (2017), Bergmann and Sams (2016), and Freire (2002). The study discusses the relevance of the flipped classroom in the development of students' autonomy, creativity, and protagonism, as well as the challenges faced in its implementation, especially in the Brazilian context, marked by inequalities in access to technological resources. The results indicate that the flipped classroom contributes to more dynamic and interactive learning, by shifting the focus from theoretical exposition to artistic practice in the classroom. However, the application of this methodology requires adaptation to the material conditions of students, in addition to continued training of teachers to deal with new pedagogical demands. The research concludes that, although the flipped classroom is a promising strategy, its full adoption in arts education depends on institutional support, equitable access to technology and adaptation to the socioeconomic realities of students.